Combined lung-kidney transplantation: First case in Portugal. (2021) - Silva, David T.; Dantas, Carolina; Santos, Ana Sofia; Silva, Cecilia; Aires, Inês; Remédio, Francisco; Carrelhas, Sofia; Pena, Ana; Reis, João Eurico; Calvinho, Paulo; Semedo, Luísa; Cardoso, João; et al.
Abstract: A significant dysfunction of another organ is usually considered an absolute contraindication for lung transplantation, unless multiorgan transplantation is indicated and practical, as is the case of combined lung-kidney transplantation. Few cases of combined lung-kidney transplantation have been described in the literature; however, it is known that, in certain cases, it is the only way to offer an opportunity to selected patients with renal and lung dysfunction. The authors are not aware of any previously published case of a patient receiving both extracorporeal membrane oxygenation and continuous venovenous hemodiafiltration as a bridge for combined kidney-lung transplantation. The authors present the first case of combined lung-kidney transplantation performed in Portugal.